2021
DOI: 10.1021/acs.est.0c05164
|View full text |Cite
|
Sign up to set email alerts
|

Transformation and Mobility of Cu, Zn, and Cr in Sewage Sludge during Anaerobic Digestion with Pre- or Interstage Hydrothermal Treatment

Abstract: Anaerobic digestion (AD) combined with hydrothermal treatment (HT) is an attractive technology for sewage sludge treatment and resource recovery. The fate and distribution of heavy metals in the sludge during combined HT/AD significantly affect the sludge final disposal/utilization options, yet such information is still lacking. This study systematically characterizes the transformation of important heavy metals Cu, Zn, and Cr in sewage sludge during AD with pre- or interstage HT (i.e., HT-AD or AD-HT-AD, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Secondary wastewater effluent was then added to reach a total liquid volume of 400 ml. As mentioned above, instead of pre‐reduced medium, secondary wastewater effluent was used to avoid any interference from the medium as the digestates at the end of the incubation for the BMP tests I and II were used in a companion, parallel study which assessed the speciation of several elements (nutrients and metals) (Wang et al, 2021; Wang, Zhang, Liu, et al, 2020; Wang, Zhang, Patel, et al, 2020). Preliminary experiments showed that substituting secondary wastewater effluent for medium in BMP tests did not significantly affect the rate and extent of methane production (data not shown).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary wastewater effluent was then added to reach a total liquid volume of 400 ml. As mentioned above, instead of pre‐reduced medium, secondary wastewater effluent was used to avoid any interference from the medium as the digestates at the end of the incubation for the BMP tests I and II were used in a companion, parallel study which assessed the speciation of several elements (nutrients and metals) (Wang et al, 2021; Wang, Zhang, Liu, et al, 2020; Wang, Zhang, Patel, et al, 2020). Preliminary experiments showed that substituting secondary wastewater effluent for medium in BMP tests did not significantly affect the rate and extent of methane production (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…For the AD-HT-AD configuration, in order to obtain predigested sludge, the first batch AD was carried out in a 9-L glass reactor with a liquid volume of 6 L, which contained (initial values): sludge mixture (see Table 1), 10 g volatile solids (VS)/L; anaerobic inoculum, 1 g VS/L; secondary wastewater effluent, 4.15 L; and NaHCO 3 , 1.4 g/L. It should be noted that instead of pre-reduced medium, secondary wastewater effluent was used because the digestates at the end of the incubation were used to assess the speciation of several elements (nutrients and metals) in a companion, parallel study without any interference from the medium Wang, Zhang, Jung, et al, 2021). For the same reason, a low VS-based inoculum-to-substrate ratio (ISR) of 1:10 was chosen to avoid over diluting the sludge mixture.…”
Section: Preparation Of Pre-digested Sludgementioning
confidence: 99%
“…With the recent development of an atomic-resolution transmission electron microscope (AC-TEM) and X-ray absorption fine structure (XAFS), direct visualization of single atoms has become feasible and regular. More adsorption dynamic details, which might be ignored with traditional empirical adsorption models, could be directly visible now. These advancements, together with other techniques, provide an excellent opportunity to directly visualize the adsorption behavior on a material surface and open a new era to study the adsorption dynamics on the material interface.…”
Section: Introductionmentioning
confidence: 99%
“…More than 10 million dry tons of sewage sludge are generated annually as a byproduct of publicly owned municipal wastewater treatment works in the United States. Sewage sludge generally consists of a significant portion of organic matter (OM), phosphorus (P), and nitrogen (N), providing great opportunities for energy recovery via biomethane production and recycling/reclamation of nutrients. , However, sewage sludge also contains toxic metals (e.g., Cu, Zn, and Cr) and organic pollutants (e.g., polycyclic aromatic hydrocarbons (PAHs) and polychlorinated dibenzofurans (PCDFs)), along with pathogenic bacteria. Thus, the management of sewage sludge must integrate resource recovery and safe disposal to achieve societal and environmental sustainability.…”
Section: Introductionmentioning
confidence: 99%